Fast injection and extraction kicker system design for High rEpetition rate Muon Source at CSNS. (3rd August 2021) - Lin, M.N.; Wu, Y.W.; Huang, L.S.; Zhang, W.Q.; Li, H.B.; Liu, Y.T.; Li, J.; Huang, Y.; Zhao, G.D.; Deng, C.D.; Wu, G.S.; Chen, C.; et al.
Abstract: A non-parasitic muon production facility (HEMS, abbreviation of High rEpetition rate Muon Source) at China Spallation Neutron Source (CSNS) is proposed. HEMS will extract a 500 MeV proton beam from a proton storage ring with a circumference of 80 m to bombard a target on a linear section at a repetition rate of 100 Hz. After bombarding the target, the beam will be injected back into the proton storage ring. The proton beam will be extracted and injected repeatedly to the proton storage ring 20 times within 20 ms. For injection and extraction kicker system, the repetition rate of pulser should be as high as 1 kHz. In addition, to achieve a large kick angle with a high magnet gap aperture in a relatively small beam lattice, kicker pulser is required to generate a large excitation current. The primary challenge is to build a high repetition rate, high current, and fast injection and extraction kicker system. To achieve these requirements, a 6.25 Ω impedance matching kicker system, mainly composed of a twin-C transmission line kicker magnet and inductive adder, is developed. In this paper, we report the conceptual design of the kicker magnet and kicker pulser for HEMS.